There is a common integration trick when evaluating indefinite integrals , namely, ∫ e x ( f ( x ) + f ′ ( x ) ) d x = e x f ( x ) + C .
Hence, or otherwise, calculate
∫ 0 1 e x ( 2 5 6 x 1 5 − x 1 7 − x 1 6 ) d x .
Clarification: C denotes the arbitrary constant of integration .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You have missed d x at the back.
Let f ( x ) = a x 1 7 + b x 1 6 , then f ′ ( x ) = 1 7 a x 1 6 + 1 6 b x 1 5 ; and:
f ( x ) + f ′ ( x ) a x 1 7 + b x 1 6 + 1 7 a x 1 6 + 1 6 b x 1 5 a x 1 7 + ( b + 1 7 a ) x 1 6 + 1 6 b x 1 5 = 2 6 5 x 1 5 − x 1 7 − x 1 6 = 2 6 5 x 1 5 − x 1 7 − x 1 6 = 2 6 5 x 1 5 − x 1 7 − x 1 6
Equating the coefficients on both sides, we get a = − 1 and b = 1 6 . Therefore, f ( x ) = 1 6 x 1 6 − x 1 7 and we have:
∫ 0 1 e x ( 2 5 6 x 1 5 − x 1 7 − x 1 6 ) d x = e x ( 1 6 x 1 6 − x 1 7 ) ∣ ∣ ∣ ∣ 0 1 = e ( 1 6 − 1 ) = 1 5 e
Problem Loading...
Note Loading...
Set Loading...
∫ e x [ 2 5 6 x 1 5 − x 1 7 − x 1 6 ] d x = ∫ e x [ 2 5 6 x 1 5 + 1 6 x 1 6 − x 1 7 − 1 7 x 1 6 ] d x = − x 1 6 e x ( x − 1 6 ) + c